2020
DOI: 10.1039/c9cp06473g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anion reorientation on proton mobility in the solid acids family CsHyXO4(X = S, P, Se,y= 1, 2) fromab initiomolecular dynamics simulations

Abstract: The high temperature phases of the solid acids CsHSeO4, CsHSO4 and CsH2PO4 show extraordinary high proton conductivities, which are enabled by the interplay of high proton transfer rates and frequent anion reorientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…In addition, two properties were examined in this study: the lifetime of the ionic state of H n PO 4 (3Àn)À (n = 0, 1, 2, 3, or 4) and the reorientation time averaged over all H n PO 4 (3Àn)À . Previous FPMD studies 14,19,22 have indicated a significant contribution of the Grotthuss mechanism in the liquid PA. In this mechanism, proton hopping between PA anions and their reorientations strongly affect the proton diffusivity.…”
Section: Production Runsmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, two properties were examined in this study: the lifetime of the ionic state of H n PO 4 (3Àn)À (n = 0, 1, 2, 3, or 4) and the reorientation time averaged over all H n PO 4 (3Àn)À . Previous FPMD studies 14,19,22 have indicated a significant contribution of the Grotthuss mechanism in the liquid PA. In this mechanism, proton hopping between PA anions and their reorientations strongly affect the proton diffusivity.…”
Section: Production Runsmentioning
confidence: 97%
“…Similar to a previous study, 22 the reorientation time averaged over all H n PO 4 (3Àn)À was calculated from the autocorrelation function:…”
Section: Production Runsmentioning
confidence: 99%
See 3 more Smart Citations